Qualidade de sementes, teor de nitrogênio e expressão gênica em genótipos de milho inoculados com Azospirillum brasilense - Pereira, Lívia de Matos [UNESP] (2014)
The objective was to evaluate in maize genotypes the effect of inoculation with Azospirillum brasilense in seed germination response and seedling growth, the nitrogen and chlorophyll leaf content the relative quantitative expression of ESTs keys on nitrogen metabolism. In a first experiment was evaluated the physiological quality of seeds from two single cross hybrids (AG7098 and 2B707) and two synthetic varieties experimental (V2 and V4) inoculated with A. brasilense , by germination and emergence percentage, emergence rate tests, dry weight of shoot and root The second experiment was conducted in a greenhouse where the same genotypes were grown under different forms of inoculation with A. brasilense and supplying nitrogen being evaluated nitrogen and chlorophyll leaf content and the expression of two ESTs encoding key enzymes of metabolic pathway for N, nitrate reductase (ZmNR) and glutamine synthetase (ZmGln1-3) using the technique of quantitative real -time PCR. The genotypes differ with respect to inoculation with A. brasilense. Hybrids were responsive to inoculation with A. brasilense for dry root matter. The V2 variety showed lower performance as the dry weight of root, but responded positively to dry mass of shoots and V4 showed no significant differences when inoculated. The results of chlorophyll content were not significant. To the N content each genotype evaluated responded in a particular way. Regarding the expression of ESTs were found that inoculation promoted increases in expression ZmNR for AG7098 and 2B707 hybrids. A variety V2 did not respond to inoculation and V4 showed higher expression level when received only nitrogen application. In general, the varieties responded negatively or did not respond to inoculation with A. brasilense , when comparing the genotypes within treatments , and V2 showed lower expression values ZmRN for all forms of inoculation and fertilizer ...